Pendampingan Pengembangan Literasi Melalui Sudut Baca dan Eksta Teras Mimpi dalam Meningkatkan Pendidikan di Tegalrejo Kecamatan Pulung Ponorogo - Widodo Widodo; Mariana Mariana (Institut Agama Islam Sunan Giri Ponorogo, 2025)
The mentoring program for the development of human resource potential in improving elementary school education at SDN 2 Tegalrejo in Tegalrejo Pulung Ponorogo. The problems they face are related to improving education at SDN 2 Tegalrejo, namely a lack of interest in reading, a lack of students' understanding of learning material, so this mentoring program is intended to assist SDN 2 Tegalrejo students in developing their potential. The method used to overcome these problems is the provision of reading corners, dream terraces, and teaching KPM. The results of this service provide an understanding of the importance of reading for children and the importance of children's additional learning outside of school hours.